Applications of Inventory Management in Construction Industry: Impacts and Techniques of Inventory Management in the Construction Industry (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Inventory management is the soul of Materials Management, aims at optimisation of inventory investment to ensure continuity in availability of materials. Around 60 of the firm's working capital is normally joined up in its different forms of inventory. Inventory management is the main constituent of any construction industry therefore the organization need to be familiar with the repercussions of proper material management techniques on the success of project execution. Inventories represents collection of selected items which are either held for sale in the normal track of industry or are in the process of production for sale or are yet to be utilised in the construction of supplies services, in the paper techniques for inventory management is given. Also few studies have been carry out on the inventory organization techniques its importance.